MATLAB GUI for digital communication system with tone jamming - Mathumisaranon, Thanakorn; Chayratsami, Pornpimon (My University, 2013)
This paper presents an educational tool for teaching in the signals and systems and related courses using the MATLAB Graphical User Interface (GUIs). The proposed GUI module is a simulation of the baseband digital communication system. It demonstrates the transmission of the Binary Phase Shift Keying signal over an AWGN channel with a tone jamming interference and the reduction of the jamming effect using a digital notch filter at the receiver. The output response can be selected to illustrate the differences of the signal corresponding to each section of the communication system. These GUls are thoroughly explained in the paper. © 2013 IEEE.
Keywords: Digital Communications; MATLAB GUI; Notch filter; Simulation; Tone jamming